Cost-effectiveness of Hepatitis C Virus Treatment Models for People Who Inject Drugs in Opioid Agonist Treatment Programs. (16th May 2019) - Gutkind, Sarah; Schackman, Bruce R; Morgan, Jake R; Leff, Jared A; Agyemang, Linda; Murphy, Sean M; Akiyama, Matthew J; Norton, Brianna L; Litwin, Alain H; Linas, Benjamin P
Abstract: Background: Many people who inject drugs in the United States have chronic hepatitis C virus (HCV). On-site treatment in opiate agonist treatment (OAT) programs addresses HCV treatment barriers, but few evidence-based models exist. Methods: We evaluated the cost-effectiveness of HCV treatment models for OAT patients using data from a randomized trial conducted in Bronx, New York. We used a decision analytic model to compare self-administered individual treatment (SIT), group treatment (GT), directly observed therapy (DOT), and no intervention for a simulated cohort with the same demographic characteristics of trial participants. We projected long-term outcomes using an established model of HCV disease progression and treatment (hepatitis C cost-effectiveness model: HEP-CE). Incremental cost-effectiveness ratios (ICERs) are reported in 2016 US/quality-adjusted life years (QALY), discounted 3% annually, from the healthcare sector and societal perspectives. Results: For those assigned to SIT, we projected 89% would ever achieve a sustained viral response (SVR), with 7.21 QALYs and a 245 500 lifetime cost, compared to 22% achieving SVR, with 5.49 QALYs and a 161 300 lifetime cost, with no intervention. GT was more efficient than SIT, resulting in 0.33 additional QALYs and a 14 100 lower lifetime cost per person, with an ICER of 34 300/QALY, compared to no intervention. DOT was slightly more effective and costly than GT, with an ICER > 100 000/QALY, compared to GT. In probabilistic sensitivity analyses, GT and DOT were preferred in 91% of simulations at a threshold of <100 000/QALY; conclusions were similar from the societal perspective. Conclusions: All models were associated with high rates of achieving SVR, compared to standard care. GT and DOT treatment models should be considered as cost-effective alternatives to SIT. Abstract : We analyzed the cost-effectiveness of self-administered individual treatment (SIT), group treatment (GT), and directly observed therapy (DOT) for hepatitis C in opiate agonist treatment programs using trial results. GT and DOT models were found to be cost-effective alternatives to SIT.